Framing ethnicity under conditions of uncertainty: the case of Hazaras during Afghanistan's 2014 presidential elections. Issue 6 (1st November 2016) - Ibrahimi, Niamatullah
Abstract: This article focuses on Hazaras to explore the dynamics of ethnic mobilisation during the 2014 presidential election in Afghanistan. It emphasises the communicative and interactive nature of ethnic identification as a product of the historical experiences of Afghanistan's various ethnic communities with the state. The article analyses the election manifestos, speeches and campaign materials of the two leading candidates to identify their main communicative and discursive strategies. It finds that candidates employed Islam, ideas of national identity and specific ethnic concerns as discursive resources to appeal to elites and voters at different levels. It argues that ethnic identities as a framework for political mobilisation are closely linked to dynamics of state-building, especially the centralisation of political power and pervasive uncertainties which result from contestation over control of the state.